A critical companion to Julie Taymor (Critical companions to contemporary directors, 2024)
"Contributors to this collection examine issues of creativity, gender, sexuality, and adaptation by focusing on themes from Julie Taymor's oeuvre including martyrdom, musicality, fidelity, postmodern representations, feminism and queerness, identity, desire, trauma, revenge, hybridity, and obscenity"--